Synergistic Impacts of Microplastics and Heavy Metals in Aquatic Environments and Strategies for Mitigation - Prachi Siddharth Bagde; Javed Gafur Khan Pathan (Journal of Indian Fisheries Association, 2024)
One increasing environmental concern is the extensive pollution of aquatic habitats by heavy metals and microplastics. Oceans, estuaries, lakes, and even deep-sea sediments are contaminated by microplastics, which are now found from the polar regions to the equator. They come from both primary sources, like synthetic fabrics, and secondary sources, like the breakdown of bigger plastic waste. Heavy metals, introduced through industrial, agricultural, and urban activities, interact with these microplastics, particularly after the particles undergo physical and chemical weathering in aquatic environments. The surface area, size, and type of polymer of the microplastics, as well as the water's salinity and pH, all affect these interactions. This article examines the complex dynamics between microplastics and heavy metals, shedding light on their combined impact on aquatic ecosystems and the broader implications for environmental health